FACTORS AFFECTING THE ADOPTION OF INVENTORY COST FLOW METHOD BY THE MACEDONIAN COMPANIES: FIFO, WEIGHTED AVERAGE, AND SPECIFIC IDENTIFICATION METHOD - STEVCEVSKA SRBINOSKA, Dusica; LJAMOVA, Angela; HRISTOVA, Snezhana (Studia Universitatis Babeș-Bolyai Negotia, 2020)
Inventory valuation is a major topic in the accounting practice. Inventory valuation is reflected in financial reporting, i.e. the balance sheet and the profit and loss account and the choice of the right inventory cost flow method is one of the basic decisions all companies engaged in manufacturing and distribution of goods need to make. Preferably, the chosen method should result in the best income and financial result measurement. However, no method is acknowledged to always be the best for accomplishing these objectives. The main aim of this paper is to investigate the factors affecting the adoption of inventory cost flow method by Macedonian companies. The data was collected by using a questionnaire randomly distributed via email to Macedonian retailing and manufacturing companies and later examined through statistical methods. Analyzing a pool of 56 respondents, we find that the subject of inventory valuation is important as most of the participants consider that they understand the existing inventory valuation methods. The choice of inventory valuation method is mostly affected by the level of education of the manager, understanding of the method and simplicity of the separate inventory valuation methods. JEL classification: M4, M1